Aspek Hukum Implikasi Penyusutan Peran Notaris Terhadap Pengurusan Perseroan Terbatas - Razin Ardi Shidiq; Rahmi Zubaedah (Jurnal Ilmiah Wahana Pendidikan, 2022)
The Job Creation Law explains that individual legal entities that meet the criteria for Individual Companies or Micro and Small Enterprises as a form of PT, furthermore PP No. 8 of 2021 provides rules that Individual Companies are established by registering and filling out a Statement of Establishment, and similar to dissolution or amendment, this means that it is carried out without a Notarial Deed. This research aims to understand and further examine the implications of the absence of a Notarial Deed on the sustainability of the Company will affect the implementation of Individual Companies in Indonesia. This research is normative legal research using literature approach techniques. So the conclusion is that the provisions in Article 7 paragraph (7) of Law No. 40 of 2007 jo. Article 109 of the Job Creation Law does not provide an exception to the provisions regarding the pouring of articles of association in the form of a Notarial Deed, so it is not in line with article 153A paragraph (2) Job Creation Law. The Notarial Deed is only required to be prepared regarding an Individual Company that needs to be changed to a Company. Provisions that are not stated in the Statement of the Individual Company comply with the laws and regulations.